(untitled) (Journal of Hama University, 2024)
The aim of this research is to recognize the effect of recreational sports activities on the level of emotional intelligence in women who are not sports practices, and the differences in the effect of such activities depending on several variables: "social status", "children", "work". This research used the Bar-on scale of emotional intelligence, which was distributed to a sample of 25 women who did not engage in any sporting activity before and after a recreational sports activity (Zumba, Aerobic) for two months. The results of the study indicated that the exercise of recreational sports activity improved their level of emotional intelligence, and that there were no differences in the level of such intelligence depending on previous variables.